(3eLehYI aj GdgfOSIs - (3KGhRhSjhSs
(3ChdgG (B:s
(3hgh KdGK ebGdGJ hJSYI hNeShf TcdkG hai HYV GdfSN fbUkG Tcd ai GdYOO hbO CeQ Hfbdg ef GdjhfGfjI Edi GdYQHjI s
(3BNQgG (B:s
(3hcGf CQ eYdhekG acd hGMO ef eYdhe hLejY G M eYdhe hPdc eG CQOfGg Je Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3CeQ HJQLeI CHh GdYHGS CMeO Hf GdeYJUe HGddg HgG CTcGd gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B142s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs